2020
DOI: 10.1364/oe.410338
|View full text |Cite
|
Sign up to set email alerts
|

Chromaticity of structural color in polymer thin film photonic crystals

Abstract: A three-dimensional goniometric study of thin-film polymer photonic crystals investigates how the chromaticity of structural color is correlated to structural ordering. Characterization of chromaticity and the angular properties of structural color are presented in terms of CIE 1931 color spaces. We examine the viewing angle dependency of the Bragg scattering cone relative to sample symmetry planes, and our results demonstrate how increased ordering influences angular scattering width and anisotropy. Understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…In agreement with earlier reports [16,17,30], it is seen that a larger strain is able to increase both the equilibrium level of ordering and also the speed of crystallization. A large shearing force on the polymer opal provides more stored elastic energy to facilitate sphere rearrangement with respect to a constant activation energy threshold.…”
Section: Strain Amplitude (σ) Dependencesupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with earlier reports [16,17,30], it is seen that a larger strain is able to increase both the equilibrium level of ordering and also the speed of crystallization. A large shearing force on the polymer opal provides more stored elastic energy to facilitate sphere rearrangement with respect to a constant activation energy threshold.…”
Section: Strain Amplitude (σ) Dependencesupporting
confidence: 92%
“…This generates strong shearing forces inside the PO purely parallel to the surface and resultant strains of magnitude up to 300%. Multiple reported crystallographic and microscopic characterizations [17,29,30] have repeatedly confirmed a random hexagonal packing arrangement, with some in-plane layering, and a progressive development of ordering through the structure from the surfaces. The final PO thin films show exceptional mechanical robustness, flexibility, and stretchability (>100%), allowing for the tuning of optical properties by viscoelastic deformation [19,31].…”
Section: Introductionmentioning
confidence: 89%
“…Corresponding image analysis is reported on in Figure A2, which probes the structural features of the correlation length and packing quality. This work is in excellent agreement with the many previous structural studies on polymer opals as reported elsewhere [25,29,34].…”
Section: Structural Characterizationsupporting
confidence: 92%
“…This structural color becomes highly intense for 40 BIOS passes (Figure 4d), and the scattering cone was significantly widened with an angular full width half maximum (FWHM) of 32.5 • as described in Table 1. We previously reported on the change in spatial frequency of the constituent nanoparticle arrays using Lomb periodogram Fourier transform methods and determined the sharpness of the distribution of these frequencies [29]. The change in the ratio of the distribution sharpness to frequency was a clear indicator of the improving ordering, which has previously [29] been seen to correlate with increases in the full width half maximum of the structural color scattering cone.…”
Section: Reflectance Characterizationmentioning
confidence: 96%
See 1 more Smart Citation